2017
DOI: 10.1080/87559129.2017.1307389
|View full text |Cite
|
Sign up to set email alerts
|

Is air-drying of plant-based food at low temperature really favorable? A meta-analytical approach to ascorbic acid, total phenolic, and total flavonoid contents

Abstract: Velichová (2017): Is airdrying of plant-based food at low temperature really favorable? A meta-analytical approach to ascorbic acid, total phenolic and total flavonoid contents, Food Reviews International,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 58 publications
1
0
0
Order By: Relevance
“…From evaluated samples, Miel presented a high content of AA despite having been dehydrated at a higher temperature, compared with the Esmeralda and Cayenne varieties, which presented a content lower than 55 mg/100 g, and it was to be expected because the time of exposure to heat was 15 h, while for Esmeralda and Cayenne 2 the exposure to high temperature was 20 and 18 h, respectively; The quantity of pineapple that was dehydrated was also greater, 20 and 36 kg of pulp, respectively. Similar results are reported for pineapple dehydrated at 60°C, slices 10 mm thick, and dehydration for 13 h, with a final AA content of 101 mg/100 g (Mühlbauer & Müller, 2020 ); and correlating this phenomenon in tomato with slices of 11 mm at a temperature of 6°C and exposure time between 16 and 20 h, a loss of AA between 30% and 40% was recorded (Khazaei et al, 2008 ), the above also coincides with what was reported by 40 studies of various dehydrated foods, where 43% lost between 21.8% and 53% of AA under similar dehydration conditions (60°C) (Červenka et al, 2018 ). It should be mentioned that although pineapple is not within the aforementioned studies, it is characterized as an important source of bioactive compounds that include antioxidants such as ascorbic acid, flavonoids, phenolic compounds, and pectins that are important for nutrition (Ghasemi et al, 2009 ; Kumar et al, 2021 ; Montero‐Calderón, 2010 ).…”
Section: Resultssupporting
confidence: 73%
“…From evaluated samples, Miel presented a high content of AA despite having been dehydrated at a higher temperature, compared with the Esmeralda and Cayenne varieties, which presented a content lower than 55 mg/100 g, and it was to be expected because the time of exposure to heat was 15 h, while for Esmeralda and Cayenne 2 the exposure to high temperature was 20 and 18 h, respectively; The quantity of pineapple that was dehydrated was also greater, 20 and 36 kg of pulp, respectively. Similar results are reported for pineapple dehydrated at 60°C, slices 10 mm thick, and dehydration for 13 h, with a final AA content of 101 mg/100 g (Mühlbauer & Müller, 2020 ); and correlating this phenomenon in tomato with slices of 11 mm at a temperature of 6°C and exposure time between 16 and 20 h, a loss of AA between 30% and 40% was recorded (Khazaei et al, 2008 ), the above also coincides with what was reported by 40 studies of various dehydrated foods, where 43% lost between 21.8% and 53% of AA under similar dehydration conditions (60°C) (Červenka et al, 2018 ). It should be mentioned that although pineapple is not within the aforementioned studies, it is characterized as an important source of bioactive compounds that include antioxidants such as ascorbic acid, flavonoids, phenolic compounds, and pectins that are important for nutrition (Ghasemi et al, 2009 ; Kumar et al, 2021 ; Montero‐Calderón, 2010 ).…”
Section: Resultssupporting
confidence: 73%